2004
DOI: 10.1079/bjn20041272
|View full text |Cite
|
Sign up to set email alerts
|

Description and validation of the ActiReg®: a novel instrument to measure physical activity and energy expenditure

Abstract: The ActiReg w (PreMed AS, Oslo, Norway) system is unique in using combined recordings of body position and motion alone or combined with heart rate (HR) to calculate energy expenditure (EE) and express physical activity (PA). The ActiReg w has two pairs of position and motion sensors connected by cables to a battery-operated storage unit fixed to a waist belt. Each pair of sensors was attached by medical tape to the chest and to the front of the right thigh respectively. The collected data were transferred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(116 citation statements)
references
References 30 publications
5
110
1
Order By: Relevance
“…Experiments with ActiReg w and DLW have shown that in individuals with PAL . 2.0, measurement of heart rate should be included to improve the calculation of EE 24 . However, only a few people in the Danish population have a PAL .…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with ActiReg w and DLW have shown that in individuals with PAL . 2.0, measurement of heart rate should be included to improve the calculation of EE 24 . However, only a few people in the Danish population have a PAL .…”
Section: Discussionmentioning
confidence: 99%
“…Wires from the accelerometer are attached to arm and leg. It is a reliable instrument to assess energy expenditure, but mounting of the instrument should be done by the same experienced person, which makes it less suitable in large scale studies (Arvidsson D et al, 2006;Hustvedt BE et al, 2004).…”
Section: Other Instrumentsmentioning
confidence: 99%
“…The ActiReg is using combined recordings of body position and motion to measure physical activity (Hustvedt et al 2004) and consists of two pairs of position and motion sensors connected by cables to a storage unit fixed to a waist belt.…”
Section: Total Energy Expenditure -Measuredmentioning
confidence: 99%